Lung Abscess Carcinomatous - Upi Puspita; Fauzar; Roza Kurniati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction: Pulmonary malignancies may easily be overlooked and valuable time may be lost. Lung cancer is sometimes diagnosed as a tuberculous cavity or an abscess. Abscess formation can appear in several different ways. Carcinoma that occurs in medium-sized bronchi causes partial bronchial obstruction, atelectasis, and infection due to retention. Inflammation can progress to damage to lung tissue, resulting the formation of multiple suppurative foci or more localized lung abscess. The link between lung abscess and lung cancer has been known, but the presence of malignancy in lung abscesses often undiagnosed. Obstruction from lung cancer can predispose to the development of a lung abscess. Case of a 54 year old man with increased pain at the right chest when breathing in since two months. On physical examination, it was found decreased of fremitus at the right hemithorax, deafness and decreased breath sounds as high as the II - V thoracic right hemithorax. Thorax CT-scan showed a round, homogeneous (HU: 17-30), with a cavity-like image with air fluid level, size: 7,88 cm x 8,2 cm x 9,29 cm and honey comb appearance around it. On the examination of TTNA (Transthoracic Needle Aspiration) results obtained Squamous Cell Carcinoma. A lobectomy is planned for the patient. Conclusion: We reported a rare case, a 54 year old male patient, with the diagnosis of Carcinomatous Lung Abscess. This case report was prepared with the aim of increasing awareness of malignancy in patients with a clinical presentation of abscesses, especially in old age.